Promoting English Pronunciation Skill for Elementary Students at MI Azharul Ulum Through Audio Lingual Method - Rohmah, Ainur; Akmalia, Atiqatul; Syarifah, Nisrin Raudha; Ainiyah, Nur Rohmatul; Mulis (Institut Agama Islam Tarbiyatut Tholabah, 2024)
This current research was employed to solve students’ obstacles related to Pronunciation. This research was conducted in the fifth grade of MI Azharul Ulum Brongkal 03 consisting of 30 students. Classroom Action Research was used in this research where it utilized two cycles and each cycle consisted of two meetings. Some instruments were used to collect the data such as tests (preliminary and post-test). The test included pre-tests and post-tests in which it was applied to acknowledge the students’ prior pronunciation skills before and after the teaching and learning process by using the Audio Lingual Method method. To analyze the data, researchers employed a scoring rubric adapted from Fajriyah (2011) which included (5) Phonetically Correct, Almost error free, Awareness of Accent (4) Comprehensible, generally correct, occasional error (3) Frequent errors that confuse listener (2) Many errors that interfere with comprehensibility (1) Most utterances contain errors, incomprehensible. The finding revealed that in a preliminary test, the students obtaining a minimum mastery criterion (KKM) was 16,66%. It indicated the students’ pronunciation was poor. Yet, for the first cycle, the students obtaining a minimum mastery criterion (KKM) was 40,00%. The first cycle showed an improvement in students’ pronunciation progress. While for the second cycle, the students obtaining a minimum mastery criterion (KKM) was 66,66%. Hence, this research highlighted and recommended Audio Lingual Method strategy should be applied when teaching pronunciation ability.